Meridional and zonal changes in water properties along the continental slope off central and northern Chile - Llanillo, P. J.; Pelegrí Llopart, José Luis; Duarte, Carlos M.; Emelianov, Mikhail; Gasser Rubinat, Marc; Gourrion, J.; Rodriguez-Santana, A. (2013)
The Humboldt-09 cruise covered a narrow meridional band along the Chilean continental slope (44?23º S). Here we use physical\nand biochemical data from a long meridional section (4000 km) and three short zonal sections (100 km) to describe the distribution of the\ndifferent water masses found in this region. Six water masses were identified: Subantarctic Water (SAAW), Summer Subantarctic Water\n(SSAW), Subtropical Water (STW), Equatorial Subsurface Water (ESSW), Antarctic Intermediate Water (AAIW), and Pacific Deep Water\n(PDW). For the first time, a novel set of source water mass properties (or water types) is introduced for SSAW, and nutrient and dissolved\noxygen water types are proposed for all the water masses. Optimum multiparameter (OMP) analysis was used through an iterative process to\nobtain a sound definition of the water types that minimizes the residuals of the method. Both the classic OMP and the quasi-extended OMP\nmodels reproduced the data rather well. Finally, the spatial distribution of the different water masses was calculated with the quasi-extended\nOMP, which is not influenced by the respiration of organic matter. The distribution of the different water masses is presented over the\nmeridional and zonal transects and in property-property diagrams. A smooth meridional transition from subantarctic to tropical and equatorial\nwater masses is observed in this area. This transition takes place in surface, central, and intermediate waters over distances of the order of 1000\nkm. The meridional transition contrasts with the abrupt zonal changes found in the cross-slope direction, which are of comparable magnitude\nbut over distances of the order of 100 km. Both AAIW and SAAW (fresh and well oxygenated) partially mix with the hypoxic ESSW and,\ntherefore, play an important role in the ventilation of the southern part of the oxygen minimum zone.